2012
DOI: 10.1371/journal.pgen.1002850
|View full text |Cite
|
Sign up to set email alerts
|

A Luminal Glycoprotein Drives Dose-Dependent Diameter Expansion of the Drosophila melanogaster Hindgut Tube

Abstract: An important step in epithelial organ development is size maturation of the organ lumen to attain correct dimensions. Here we show that the regulated expression of Tenectin (Tnc) is critical to shape the Drosophila melanogaster hindgut tube. Tnc is a secreted protein that fills the embryonic hindgut lumen during tube diameter expansion. Inside the lumen, Tnc contributes to detectable O-Glycans and forms a dense striated matrix. Loss of tnc causes a narrow hindgut tube, while Tnc over-expression drives tube dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 44 publications
(58 reference statements)
4
30
0
Order By: Relevance
“…In the absence of Cftr activity, the KV lumen fails to inflate, indicating that fluid acts as a force driving lumen expansion and might also promote lumen coalescence. The zebrafish gut undergoes a similar process of de novo lumen formation, beginning with inflation of multiple small lumens, followed by their coalescence into one (Bagnat et al, 2007) and a similar role in de novo lumen formation and expansion has been shown for apical membrane or secreted mucins during tubulogenesis in the vertebrate vasculature (Strilić et al, 2010) and in the ommatidium (Husain et al, 2006) and hindgut (Syed et al, 2012) in Drosophila. The role of luminal content as a driving force during tube formation is most clearly exemplified by the Drosophila tracheal system, which becomes filled with a solid chitin matrix, then liquid and finally gas during its development (Tsarouhas et al, 2007).…”
Section: Discussionmentioning
confidence: 69%
“…In the absence of Cftr activity, the KV lumen fails to inflate, indicating that fluid acts as a force driving lumen expansion and might also promote lumen coalescence. The zebrafish gut undergoes a similar process of de novo lumen formation, beginning with inflation of multiple small lumens, followed by their coalescence into one (Bagnat et al, 2007) and a similar role in de novo lumen formation and expansion has been shown for apical membrane or secreted mucins during tubulogenesis in the vertebrate vasculature (Strilić et al, 2010) and in the ommatidium (Husain et al, 2006) and hindgut (Syed et al, 2012) in Drosophila. The role of luminal content as a driving force during tube formation is most clearly exemplified by the Drosophila tracheal system, which becomes filled with a solid chitin matrix, then liquid and finally gas during its development (Tsarouhas et al, 2007).…”
Section: Discussionmentioning
confidence: 69%
“…2B) [27,29]. In tnc mutants, the hindgut tube diameter remains narrow, while overexpression of Tnc leads to diametric overexpansion in a dose-dependent fashion (Fig.…”
Section: A Non-chitinous Matrix Drives Diameter Expansion Of the Drosmentioning
confidence: 92%
“…Thus, a simple extrapolation of the findings from the Drosophila trachea is not possible based on molecular homologues. However, it was recently shown that the large luminal glycoprotein Tenectin (Tnc) forms a luminal matrix that acts to drive tube diameter expansion in the developing Drosophila hindgut [27]. The Tnc matrix spans the lumen and causes dose-dependent expansion, suggesting that it generates a luminal physical force during tube growth.…”
Section: A Non-chitinous Matrix Drives Diameter Expansion Of the Drosmentioning
confidence: 99%
See 2 more Smart Citations